South Asia’s Services Trade: Barriers and Prospects for Integration - Asif Javed (International Journal of Management, Accounting and Economics, 2019)
Services trade has gained significance in the globalized world as the volume and its impacts on growth have increased. South Asian countries are also engaging in exports of services which are vital for their respective economies. However, the regional integration is yet to be promoted as hurdles including high transportation costs, lack of cross border infrastructure and lack of regional transit existed. For services trade integration, effective utilization of regional platform, easing in movement of professionals and minimizing the investment barriers can be useful measures. South Asian economies have prospects of integration in specific sectors such as tourism and Information and Communication Technology (ICT) which can be used to enhance regional services trade ties.